Imperial Germany 1871-1918 - Lee, Stephen J., 1945- (Questions and analysis in history., 1999)
"Imperial Germany, 1871-1918 explores the rise of Germany as a nation state and European power centre, through to the humiliation of the country in the First World War. Covering both domestic and foreign policy, this key text combines historical detail, questions and analysis and evaluation of primary sources. This book provides students with a clear background and a guide to examination success."--Jacket